The Influence of Teaching and Learning Interaction on Student Success at Madrasah Aliyah Al-Iklhlas Poso - Makmur, Makmur; Taufiq, Oyan D.; Asmarini, Andini (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2025)
Teaching and learning interaction is an important factor in determining student learning success. This study aims to determine the level of teaching and learning interaction, the level of student learning success, and the influence of teaching and learning interactions on student learning success at Madrasah Aliyah Al-Iklhlas Poso. This study uses a quantitative approach with a survey method. The research population is all students of Madrasah Aliyah Al-Iklhlas Poso which is 111 people, with a sample of 55 students determined through proportionate stratified sampling techniques. Data collection was carried out through questionnaires, observations, interviews, and documentation. Data analysis using descriptive statistics and simple linear regression with the help of the SPSS program. The results showed that the teaching and learning interaction between teachers and students was in the very high category, while the success of student learning was in the medium category. The results of the regression test showed that there was a significant influence between teaching and learning interactions on student learning success, with a determination coefficient of 36.5%. These findings show that the quality of teaching and learning interactions plays an important role in improving student learning success, although there are still other factors that also affect learning outcomes. Therefore, improving the quality of educational interaction between teachers and students needs to be continuously developed as an effort to improve the quality of learning.